2018
DOI: 10.1111/1462-2920.14488
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic polyphosphate metabolism in cyanobacteria responding to phosphorus availability

Abstract: Summary Despite the crucial role of polyphosphate (polyP) in aquatic environments, its metabolism in cyanobacteria responding to nutrients is poorly understood. We investigate polyP in three cyanobacteria species, specifically unicellular picocyanobacteria, under various nutritional conditions. Our experiments show that the accumulation of polyP in cyanobacteria is strongly dynamic, depending on phosphate levels and growth stages. ‘Overplus’ uptake of phosphorus (P) during the lag phase leads to the rapid accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 57 publications
5
38
1
2
Order By: Relevance
“…To our knowledge, this is the first report that the solubilization of inorganic insoluble phosphorus is coupled with the synthesis of polyphosphate. It has been reported that polyphosphate regarded as high-energy compound could be hydrolyzed when phosphorus accumulating bacteria undergo undernourished conditions (Wan et al, 2017;Li and Dittrich, 2019;Zhong et al, 2019). Previous literatures have reported that some bacteria belonging to Acinetobacter genus harbor the ability to synthesize polyphosphate and could be regarded as phosphorus accumulating bacteria (Keating et al, 2016;Han et al, 2018).…”
Section: Deciphering Phosphorus Track During Inorganic Phosphorus Solmentioning
confidence: 99%
“…To our knowledge, this is the first report that the solubilization of inorganic insoluble phosphorus is coupled with the synthesis of polyphosphate. It has been reported that polyphosphate regarded as high-energy compound could be hydrolyzed when phosphorus accumulating bacteria undergo undernourished conditions (Wan et al, 2017;Li and Dittrich, 2019;Zhong et al, 2019). Previous literatures have reported that some bacteria belonging to Acinetobacter genus harbor the ability to synthesize polyphosphate and could be regarded as phosphorus accumulating bacteria (Keating et al, 2016;Han et al, 2018).…”
Section: Deciphering Phosphorus Track During Inorganic Phosphorus Solmentioning
confidence: 99%
“…Phytoplankton are also known to accumulate polyphosphate (polyP), a polymer containing three to hundreds of orthophosphate units. The physiological functions of polyP associated with nutrient stringency have been suggested in culture studies 12,13 . PolyP exhibits complex dynamics in cells 13,14 : when P is abundant, cells take up P in excess of what is required for growth to accumulate polyP, a process called “luxury uptake” 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The physiological functions of polyP associated with nutrient stringency have been suggested in culture studies 12,13 . PolyP exhibits complex dynamics in cells 13,14 : when P is abundant, cells take up P in excess of what is required for growth to accumulate polyP, a process called “luxury uptake” 13,14 . Cells then can use this polyP to support metabolic processes and growth when P is scarce 13,15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations